Enzyme assisted extraction of luteolin and apigenin from pigeonpea [Cajanuscajan (L.) Millsp.] leaves - Fu, Yu-Jie; Liu, Wei; Zu, Yuan-Gang; Tong, Mei-Hong; Li, Shuang-Ming; Yan, Ming-Ming; Efferth, Thomas; Luo, Hao (Food chemistry, 2008)
Luteolin and apigenin are naturally occurring flavones with a wide spectrum of pharmacological properties. In the present study, enzyme assisted extraction of luteolin and apigenin from pigeonpea leaves using commercial plant cell wall degrading enzyme preparations including cellulase, beta-glucosidase and pectinase were examined. We found that pectinase offered a better performance in enhancement of the extraction yields of luteolin and apigenin than cellulase and beta-glucosidase. The pectinase assisted extraction process was further optimized by varying different parameters such as pectinase concentration, time of incubation, pH of pectinase solution, and incubation temperature. The optimum parameters were obtained as follows: 0.4mg/ml pectinase, incubation for 18h at 30–35°C, pH of pectinase solution 3.5–4. Under the optimum conditions, the extraction yields of luteolin and apigenin achieved 0.268 and 0.132mg/g in pectinase treated sample, which increased 248% and 239%, respectively, compared with the untreated ones.